Defect-free buildings - Mann, Robert S. (McGraw-Hill, 2007)
Eliminate construction mistakes and minimize your exposure to expense and litigation with defect-free buildings. With McGraw-Hill's Defect-Free Buildings, you can rid your projects of these debilitating conflicts and protect your business against the costs, delays, and litigation they create. Packed with easy-to-understand guidelines, protocols, and checklists, this indispensable volume helps you: Determine proper construction methods and costs during planning and bidding; avoid defects in the building stages and enhance quality control; obtain the proper insurance and satisfy underwriting requirements and reduce or eliminate the threat and cost of litigation.